2019
DOI: 10.1002/ejoc.201900834
|View full text |Cite
|
Sign up to set email alerts
|

Chlorotrifluoromethylation of Terminal Olefins by Atom Transfer‐Type Radical Reaction Catalyzed by Cobalt Complexes

Abstract: A cobalt porphyrin‐catalyzed chlorotrifluoromethylation reaction of olefins is described. The use of CF3SO2Cl as the CF3 radical source and a cobalt catalyst enabled the selective addition of CF3 radicals under thermal conditions. Various functional groups such as esters and Ar–X moieties, which can be reactive with low valent transition metal catalysts, were well‐tolerated in this catalytic process. A highly functionalized alkaloid derivative was also tolerated as a substrate. As a demonstration of the bio‐in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Some bromides, however, gave intermediates prone to subsequent reactions, furnishing dehalogenated product 47 or cyclopropane 48 (Scheme B). Unactivated olefin 49 has also been explored in related studies on chlorotrifluoromethylation (Scheme C) . Although most substrates were converted using the cobalt­(II) porphyrin complex (CoClTPP), vitamin B 12 was also compatible with this transformation, and when used with an alkene derived from cinchona alkaloids, a higher diastereoselectivity was observed compared to the CoClTPP-catalyzed reaction (6.4:1 vs 1.4:1).…”
Section: C–c Bond Forming Reactions Catalyzed By Vitamin B12 and Its ...mentioning
confidence: 99%
“…Some bromides, however, gave intermediates prone to subsequent reactions, furnishing dehalogenated product 47 or cyclopropane 48 (Scheme B). Unactivated olefin 49 has also been explored in related studies on chlorotrifluoromethylation (Scheme C) . Although most substrates were converted using the cobalt­(II) porphyrin complex (CoClTPP), vitamin B 12 was also compatible with this transformation, and when used with an alkene derived from cinchona alkaloids, a higher diastereoselectivity was observed compared to the CoClTPP-catalyzed reaction (6.4:1 vs 1.4:1).…”
Section: C–c Bond Forming Reactions Catalyzed By Vitamin B12 and Its ...mentioning
confidence: 99%
“…13 C­{ 1 H} NMR (126 MHz, CDCl 3 ) δ 165.9, 133.7, 129.9, 129.3, 128.7, 125.2 (q, 1 J (C, F) = 277.2 Hz), 66.8, 50.4 (q, 3 J (C, F) = 3.0 Hz), 39.4 (q, 2 J (C, F) = 29.4 Hz). 19 F NMR (376 MHz, CDCl 3 ) δ −63.7 (t, 3 J (F, H) = 10.1 Hz) …”
Section: Methodsmentioning
confidence: 99%
“…19 F NMR (376 MHz, CDCl 3 ) δ −63.7 (t, 3 J(F, H) = 10.1 Hz). 25 ((5-Chloro-7,7,7-trifluoroheptyl)oxy)benzene (3e). Following the general procedure for halotrifluoromethylation described in this experiment, 1e (0.50 mmol, 88.1 mg) reacted to 3e (78.6 mg, 56% yield, light yellow oil), which was purified by silica gel chromatography (PE/EA = 250:1).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…More recently, Matsubara and coworkers studied the chlorotrifluoromethylation of substituted terminal olefins in the presence of highly coordinated square-planar cobalt(II) complexes, such as cobalt(II) porphyrin catalysts CoTPP (TPP= 5,10,15,20-tetraphenylporphyrinato) [ 33 ]. After checking various cobalt and copper complexes, it was found that the combination of CoClTPP and CF 3 SO 2 Na was the most efficient catalyst when the reaction was carried out in MeCN as solvent.…”
Section: Chloro- and Bromotrifluoromethylationmentioning
confidence: 99%